2021
DOI: 10.1186/s13104-021-05700-x
|View full text |Cite
|
Sign up to set email alerts
|

The omega-3 and Nano-curcumin effects on vascular cell adhesion molecule (VCAM) in episodic migraine patients: a randomized clinical trial

Abstract: Objective The purpose of this clinical trial was to examine the effect of omega-3 fatty acids (W-3 FAs), nanocurcumin and their combination on serum levels and gene expression of VCAM in patients with episodic migraine. Results In this study, 80 patients were randomly divided in to 4 groups to receive for 2 months. Both serum levels and gene expression of VCAM showed remarkable decreases after single W-3 and after combined W-3 and nanocurcumin inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
0
19
0
6
Order By: Relevance
“…Among the 19 studies reviewed here, seven of the studies did not report any adverse side‐effects due to curcumin supplementation (i.e., listed in Table 3 as “not reported”) (Abdolahi et al, 2019; Djalali, Abdolahi, et al, 2020; Djalali et al, 2021; Djalali, Djalali, et al, 2020; Dolati, Ahmadi, et al, 2018; Dolati et al, 2019; Honarvar et al, 2021). Eight studies indicated that curcumin supplementation had no adverse side‐effects on the study participants (Abdolahi et al, 2017, 2018, 2021; Ahmadi et al, 2018; Dolati, Aghebati‐Maleki, et al, 2018; Dutzmann et al, 2016; Parohan et al, 2019; Ye et al, 2018). In three studies, gastrointestinal‐related side effects (e.g., diarrhea) were reported (Baum et al, 2008; Chico et al, 2018; Ringman et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 19 studies reviewed here, seven of the studies did not report any adverse side‐effects due to curcumin supplementation (i.e., listed in Table 3 as “not reported”) (Abdolahi et al, 2019; Djalali, Abdolahi, et al, 2020; Djalali et al, 2021; Djalali, Djalali, et al, 2020; Dolati, Ahmadi, et al, 2018; Dolati et al, 2019; Honarvar et al, 2021). Eight studies indicated that curcumin supplementation had no adverse side‐effects on the study participants (Abdolahi et al, 2017, 2018, 2021; Ahmadi et al, 2018; Dolati, Aghebati‐Maleki, et al, 2018; Dutzmann et al, 2016; Parohan et al, 2019; Ye et al, 2018). In three studies, gastrointestinal‐related side effects (e.g., diarrhea) were reported (Baum et al, 2008; Chico et al, 2018; Ringman et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In the studies that assessed the effects of curcumin on migraine patients, nano‐curcumin (80 mg/day) was used alone or in combination with omega‐3 fatty acids (Abdolahi et al, 2017, 2018, 2019, 2021; Djalali, Abdolahi, et al, 2020; Djalali et al, 2021; Djalali, Djalali, et al, 2020; Honarvar et al, 2021; Soveyd et al, 2017) and CoQ10 for 2 months (Parohan et al, 2019). In these studies, several factors related to inflammation and migraine symptoms were assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, nano-curcumin supplementation significantly reduced attack frequency, headache duration, and pain severity in participants. previously, Abdolahi et al reported that nano-curcumin treatment decreased headache frequency and pain severity in migraine while did not exert a significant effect on headache duration [ 32 34 ]. Curcumin exerts its analgesic effects through the following mechanisms: downregulating of pain mediators (TNF-α, IL-6), calcitonin gene-related peptide, and substance P [ 35 ], suppressing nociceptor activity [ 36 ] and NF-κB signaling [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Sokolik [ 154 ] demonstrated that CUR-loaded liposomes reduced angiotensin-converting enzyme activity in brain-targeted regions potentiating memory recovery in rats with AD. A set of clinical trial provided evidence regarding the ability of ω -3 fatty acids and nanocurcumin combination to significantly reduce migraine attack frequency [ 155 158 ]. The drug combination was able to reduce the serum levels of VCAM and C-reactive protein (CRP) along with proinflammatory cytokines IL-1 β and IL-6, which may be the mechanism at the basis of the reported therapeutic effect [ 155 158 ].…”
Section: Curcumin Nanoformulations In Inflammatory Diseasesmentioning
confidence: 99%